2022
DOI: 10.7150/thno.63735
|View full text |Cite
|
Sign up to set email alerts
|

Tubular epithelial cell-to-macrophage communication forms a negative feedback loop via extracellular vesicle transfer to promote renal inflammation and apoptosis in diabetic nephropathy

Abstract: Background: Macrophage infiltration around lipotoxic tubular epithelial cells (TECs) is a hallmark of diabetic nephropathy (DN). However, how these two types of cells communicate remains obscure. We previously demonstrated that LRG1 was elevated in the process of kidney injury. Here, we demonstrated that macrophage-derived, LRG1-enriched extracellular vesicles (EVs) exacerbated DN. Methods: We induced an experimental T2DM mouse model with a HFD diet for four months. Renal pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 45 publications
(44 reference statements)
4
51
0
Order By: Relevance
“…29 The latest study indicated that TECs-Mφ communication, in diabetic nephropathy, forms a negative feedback loop via extracellular vesicle transfer to promote renal inflammation and apoptosis. 16 Similar to the findings, in our study we found that exosomes released from Mφ from AKI mice induced TECs injury.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…29 The latest study indicated that TECs-Mφ communication, in diabetic nephropathy, forms a negative feedback loop via extracellular vesicle transfer to promote renal inflammation and apoptosis. 16 Similar to the findings, in our study we found that exosomes released from Mφ from AKI mice induced TECs injury.…”
Section: Discussionsupporting
confidence: 91%
“…13 Recent studies have also revealed that the cross-talks between Mφ and TECs played an important role in both repair/regeneration and disease progression. [14][15][16][17] However, the specific mechanism involved in Mφ-mediated kidney injury was not fully unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, high glucose stimulation is accompanied by the production of chemokines in renal tissue, which further increases the infiltration of macrophages ( 12 ). In addition, tubular epithelial cell-to-macrophage communication could form a negative feedback loop by extracellular vesicle (EV) to induce renal inflammation and apoptosis in DN ( 57 ). Leucine-rich α-2-glycoprotein 1(LRG1)-enriched extracellular vesicles derived from lipotoxic tubular epithelial cells activate M1 macrophages, which might be via a TGFβ receptor 1 (TGFβR1)-dependent manner ( 57 ).…”
Section: Crosstalks Among Macrophages and Renal Cells In Dnmentioning
confidence: 99%
“…In addition, tubular epithelial cell-to-macrophage communication could form a negative feedback loop by extracellular vesicle (EV) to induce renal inflammation and apoptosis in DN ( 57 ). Leucine-rich α-2-glycoprotein 1(LRG1)-enriched extracellular vesicles derived from lipotoxic tubular epithelial cells activate M1 macrophages, which might be via a TGFβ receptor 1 (TGFβR1)-dependent manner ( 57 ). Macrophages-derived extracellular vesicles containing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) lead to renal tubular epithelial cell apoptosis in a TRAIL-Death receptor 5 (DR5)-dependent manner ( 57 ).…”
Section: Crosstalks Among Macrophages and Renal Cells In Dnmentioning
confidence: 99%
“…Recent studies have found that crosstalk between tubular epithelial cells and macrophages is key in regulating macrophage function (Kooten and Daha 2001;Bolisetty et al 2015;Masola et al 2018). Emerging evidence indicates that extracellular vesicles (EVs) mediate the transfer of information from tubular epithelial cells to macrophages (Lv et al 2018;Jia et al 2019;Jiang et al 2022). EVs are small membrane particles secreted by all types of cells that can carry messages via molecules such as nucleic acids and proteins to recipient cells (Colombo et al 2014).…”
Section: Introductionmentioning
confidence: 99%